Use of epistemic modality by non-native speakers of English I - Letica Krevelj, Stela (Array, 2008)
Many studies on the use of epistemic modality claim that conveying statements with an appropriate degree of doubt and certainty is, while difficult for native, particularly problematic for non-native speakers. However, research dedicated to identifying the ways second/foreign language learners qualify their claims has focused primarily on the academic writing and learners’ performance was most often measured against the work of native writers. Even though these studies showed differences in the level of assertion, frequency, and range of epistemic devices used by native and non-native writers, none of them studied the differences in terms of writers’ native language and cultural style which can also affect their performance at all linguistic sub-levels. The first aim of this study was to determine whether there is any connection between the use of epistemic modality in a foreign language and students’ cultural style and mother tongue, and the second one was to discover whether there is a connection between the frequency and range of epistemic devices used in the foreign language and students’ proficiency in that language. Using corpus methodology we have examined the use of epistemic modality in the spoken picture description task performed by the same 33 Croatian learners of English both in their mother tongue and foreign language. Performances were transcribed, converted into machine readable texts and certain samples were shortened to obtain proportionate and comparable native Croatian and English learner corpora each consisting of approximately 18, 000 words. Furthermore, a cloze test was used as a measure of participants’ English language proficiency. The quantitative analysis of the corpora showed positive correlation between frequencies and range of epistemic modality used in native and non-native language as well as the correlation between foreign language proficiency and the range of epistemic devices used. A number of issues raised in the study will be discussed.